Методика разведения комаров Aedes rossicus D. G. M. и Aedes geniculatus Oliv. (Diptera, Culicidae) - Дашкина, Н.Г.; Царичкова, Д.Б. (Вестник зоологии, 1967)
The article is devoted to the methods of cultivating of two species of Mosquitoes: Aedes rossicus and Aedes geniculatus. For the laboratory cultivating the females of Ae. rossicus which have sucked the blood, were caught in nature. Ae. geniculatus larvae were collected in the hollows of trees. The larvae are kept in big crystallizing pans, the water is aerified with the help of compressor. In order to avert the formation of bacteritic film the penicillin (50-60 un. per 100 cm3 of water) is added. A mixture of dry milk, yeast, bee-bread and hematogen is a food for Ae. rossicus larvae and for Ae. geniculatus — all above mentioned products plus a jelly of the meat-peptone agar. Imago of both species are kept under the conditions of high moisture (80-95%) and during 18 hours of day light. A copulation of Ile. rossicus takes place as usual in stews 20X20X20 cm. But for Ae. geniculatus the open-air stew-cages (100X 100X200 cm) and artificial twilight for 40-60 min. are necessary. In 2-3 days after the wings ap-pear a guinea-pig is put in each stew with the mosquitoes. The females which have suc-ked the blood are caught for ovipositions. The ovipositions are kept for 9-12 days on the moisture filter and then they are flooded with water and preserved for three months in refrigerator at a temperature of 2-5° C for the removal of a dianause.